Improvement of the Efficiency and Beam Quality of the TRIUMF Charge State Booster. Issue 1 (1st April 2022) - Adegun, J; Ames, F; Kester, O
Abstract: An Electron Cyclotron Resonance Ion Source is used as the charge state booster (CSB) at the Isotope Separator and Accelerator facility (ISAC) of TRIUMF. Since its commissioning in 2010, the source has been used to charge breed radioactive ions ranging from potassium to erbium operating in single-frequency heating mode. Under this regime, the single charge state efficiency of the booster was measured up to 6 % for noble gases and the maximum charge state of Cesium that can be measured is 27+. The rf system of the source was recently upgraded to implement the two-frequency heating using a single waveguide. Preliminary operation of the booster in a two-frequency heating mode shifted the maximum charge state of Cesium that can be measured to 30+. Another point of improvement that is being addressed is the beam extraction system of the booster. A quadrupole scan technique using a thick lens approach has been developed to measure the emittance of the extracted beam and to analyze the quality of the extraction system. Overall, the system of the CSB is currently being optimized in preparation for the detailed determination of the effect of the two-frequency heating on the beam output.